An Examination of UAS Incidents: Characteristics and Safety Considerations - Jialong Sun; Sarah Hubbard (Drones)
This paper examines the characteristics and implications of reported Unmanned Aircraft Systems (UAS) incidents in the National Aeronautics and Space Administration (NASA) Aviation Safety Reporting System (ASRS) database for UAS incidents operated by remote pilots licensed under Part 107. Characteristics examined include seasonal patterns of incidents, operational mission, and number of contributing factors, as well as crew configuration, timing of incident detection, and airspace class. Results are compared with previous research and with incident data for recreational users. The narratives for each incident are assessed to provide a greater context for the incidents and to determine how the incidents vary in different classes of airspace. Findings reveal that UAS incidents often involve multiple contributing factors, including environmental, human, equipment, and policy issues; there is an increasing prevalence of human-related issues over equipment problems compared to previous research; this reflects historic safety trends in crewed aviation. Near-miss incidents with crewed aircraft are a very real concern, particularly in Class D airspace, which often includes general aviation (GA) and helicopter operations. This research underscores the need for timely communication during urgent nighttime UAS operations as well as enhanced safety culture at both operator and organizational levels.